Enhancing Self-Assembly in Cellulose Nanocrystal Suspensions Using High-Permittivity Solvents - Bruckner, Johanna R (Langmuir : the ACS journal of surfaces and colloids, 2016)
Helical liquid crystal self-assembly in suspensions of cellulose nanocrystals (CNCs), bioderived nanorods exhibiting excellent mechanical and optical properties, opens attractive routes to sustainable production of advanced functional materials. For convenience, in most studies until now, the CNCs were suspended in water, leaving a knowledge gap concerning the influence of the solvent. Using a novel approach for aggregation-free solvent exchange in CNC suspensions, here we show that protic solvents with a high dielectric permittivity εr significantly speed up self-assembly (from days to hours) at high CNC mass fraction and reduce the concentration dependence of the helix period (variation reducing from more than 30 μm to less than 1 μm). Moreover, our computer simulations indicate that the degree of order at constant CNC content increases with increasing εr, leading to a shorter pitch and a reduced threshold for liquid crystallinity. In low-εr solvents, the onset of long-range orientational order is coupled to kinetic arrest, preventing the formation of a helical superstructure. Our results show that the choice of solvent is a powerful parameter for tuning the behavior of CNC suspensions, enhancing our ability to control the self-assembly and thereby harvesting valuable novel cellulose-based materials